5E model activities in ethnically diverse classrooms - Marina Stojanovska, Katerina Rusevska, Lambe Barandovski, Slavica Tofilovska, Vladimir M. Petruševski (Chemistry in action!, 2023)
The 5E model is an inquiry-based approach and helps students gain a full understanding of new concepts, while keeping them engaged and motivated. This model is based on constructivist learning theory, and allows students to develop new knowledge that builds on their previous concepts and scientific ideas, restructures and adds newly learned information, and at the same time develops the ability for their connection, as well as application, in everyday life. The 5E model includes five stages: engage, explore, explain, elaborate/extend, and evaluate. This paper presents a lesson plan, including several activities for the topic of gases applicable in ethnically diverse classrooms, that was developed within the project "Diversity in Science towards Social Inclusion-Non-formal Education in Science for Students' Diversity" (DiSSI), as well as guidelines for teachers regarding the procedures in each of the five phases of the 5E model. Teachers can use all or part of the suggested activities, or they can modify or add new activities according to their needs and the needs of their students.